(untitled) (Journal of Social Sciences Review, 2023)
Analyzing spelling errors committed by English as a second language (ESL) learners at secondary school level was the major purpose of the present research. Deliberating which types of spelling errors do the English learners committed and what are the causes behind the committing spelling errors was the main purpose of the current research. It was case study research design based on cross-sectional survey design in nature by applying qualitative research approach. Population for the present study was comprised all students of 10th class of the Govt. High school Kangan Pur which was situated in district Kasur. Data was collect from 45 students of the 10th class which were selected by applying purposive sampling technique via structured group interview protocol. Interview protocol was pilot tested by different English teaching experts. On the bases of their instruction, interview protocol was modified for final application. Thematic analysis was done of the gathered information. It was covered that majority of the pupils committed omission, substitution, insertion, transition spelling errors. The most committed type of spelling error is ‘omission error’. They felt difficulty in writing correct spelling due to lack of vocabulary, reading habits, development of self-concept, motivation, spelling system. Moreover, mother tongue, education system, untrained English teacher, poor reading and listening skill of students, and proofreading are the causes of committing spelling errors. The major cause of committing spelling error by English as a second language (ESL) learners at secondary school level is native language.